2016
DOI: 10.1111/bpa.12384
|View full text |Cite
|
Sign up to set email alerts
|

Common Impact of Chronic Kidney Disease and Brain Microhemorrhages on Cerebral Aβ Pathology in SHRSP

Abstract: While chronic kidney disease seems to be an independent risk factor for cognitive decline, its impact on cerebral amyloid-β (Aβ) depositions, one hallmark of Alzheimer's Disease (AD) pathology, has not been investigated. Utilizing 80 male nontransgenic spontaneously hypertensive stroke prone rats (SHRSP) at various ages (12 to 44 weeks), tubulointerstitial renal damage, prevalence of cerebral microhemorrhages and Aβ accumulations were quantified. Using age-adjusted general linear models we investigated the mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 81 publications
(94 reference statements)
0
12
0
Order By: Relevance
“…By now, there is quite common acceptance that DPA is initiated by endothelial damage and BBB breakdown , which so far is in general not considered when investigating human autopsy tissue. In DPA animal models, BBB integrity loss is commonly found in the same cortical areas affected by CAA . Furthermore, its association with cortical atrophy and cortical microinfarcts (see above) supports the idea that DPA is a mixed cortical‐subcortical instead of a pure subcortical condition.…”
Section: Interaction Between Dpa and Caa – Pathophysiological Considementioning
confidence: 55%
“…By now, there is quite common acceptance that DPA is initiated by endothelial damage and BBB breakdown , which so far is in general not considered when investigating human autopsy tissue. In DPA animal models, BBB integrity loss is commonly found in the same cortical areas affected by CAA . Furthermore, its association with cortical atrophy and cortical microinfarcts (see above) supports the idea that DPA is a mixed cortical‐subcortical instead of a pure subcortical condition.…”
Section: Interaction Between Dpa and Caa – Pathophysiological Considementioning
confidence: 55%
“…Amyloid-related pathology and hypertensive cerebral small vessel disease have synergistic effects on the progression of lobar microbleeds [15]. There is also evidence from animal studies for an age-independent effect of tubulointerstitial kidney damage on brain Aβ accumulation, which can be reinforced by the co-presence of cerebral microhemorrhages [16].…”
Section: Case Presentationmentioning
confidence: 99%
“…It has been shown that CKD leads to cardiovascular disease (4), stroke (5) and decreased locomotor activity (6). Individual's quality of life can be further decreased by sexual dysfunction (7), neurological and mental disorders including anxiety and depression (7)(8)(9)(10)(11), as well as cognitive impairment (12)(13)(14)(15)(16)(17) or epileptic seizures (18), all of which lead to increased socio-economic burden of affected people (19). Although, the exact pathophysiological mechanisms underlying the neurological complications of CKD remain unclear, there are several factors that might play a role, e.g., uremic encephalopathy (20), oxidative stress (21)(22)(23) and inflammation (21,22).…”
Section: Introductionmentioning
confidence: 99%